Indonesian Older Adults’ Mental Health: An Overview - Hanum, Lathifah; Utoyo, Dharmayati B.; Jaya, Edo Sebastian (Psychological Research on Urban Society, 2018)
Many studies have been conducted on the prevalence of common psychological problems among older adults, but most of them were in a Western setting. This study aims to provide some data on the mental health of Indonesian older adults, specifically those related to stress, chronic pain acceptance, depression, and insomnia. Results show a high prevalence of psychological problems among older Indonesian adults, which is comparable to the findings of Western studies. This means that these older adults are at risk for psychological disorders; 46.28% experienced stress, 31.72% were depressed, 33.69% suffered from insomnia, and 16.84% had difficulty dealing with chronic pain. However, access to psychological services in Indonesia remains far below the Western standard.